Foundations of business communication : an integrative approach - Young, Dona J (McGraw-Hill/Irwan, 2006)
Includes bibliographical references and index.; Foundations of Business Communication uses a selection of margin boxes including Coaching Tips and Communication Challenges to reinforce the hands-on techniques of communication in an increasingly arms-length and borderless environment. BusinessWeek cases and related assignments provide real-world exposure and support.